Antimicrobial Resistance, Virulence Profiles, and Public Health Significance of Enterococcus faecalis Isolated from Clinical Mastitis of Cattle in Bangladesh. (27th September 2022) - Bag, Md. Abdus Sattar; Arif, Mohammad; Riaz, Sonia; Khan, Md. Shahidur Rahman; Islam, Md. Shafiqul; Punom, Sadia Afrin; Ali, Md. Wohab; Begum, Ferdousi; Islam, Md. Saiful; Rahman, Md. Tanvir; Hassan, Jayedul
Abstract : This study was designed to identify Enterococcus faecalis from clinical mastitis of cattle and determine their antimicrobial resistance and virulence determinants to evaluate their potential public health significance. A total of 105 composite milk samples (80 from cattle with clinical mastitis and 25 from apparently healthy cattle) were analyzed. E. faecalis were isolated by culturing on enterococcal selective media and identified by PCR and sequencing. Antimicrobial resistance phenotype was elucidated by the disc diffusion method, and MIC was determined by broth microdilution method according to CLSI guidelines. Detection of antimicrobial resistance and virulence genes was done by PCR. E. faecalis were isolated from 11.25% (9/80) of the clinical mastitis and 4% (1/25) of the apparently healthy cattle milk samples. The disc diffusion test revealed 40% isolates as resistant to tetracycline and azithromycin, respectively. Among them, 20% (2/10) of isolates showed resistance to both tetracycline and azithromycin. Tetracycline-resistant isolates showed MIC ranging from ≥64 to >128  μ g/ml and carried tetracycline-resistant genes tetK, tetL, and tetM in 25%, 25%, and 50% of the resistant isolates, respectively. On the other hand, all the isolates were sensitive to amoxicillin, ampicillin, bacitracin, chloramphenicol, gentamicin, penicillin, and vancomycin. In addition, the isolates carried at least one of the nine virulence genes screened with pil having the highest frequency, followed by fsrB, fsrC, ace, sprE, gelE, and agg genes. Positive correlations were evident between ace, fsrC, gelE, and sprE genes that are associated with the attachment and biofilm formation in E. faecalis. E. faecalis isolated in this study carried antibiotic resistance and virulence determinants which explain their competence to be potential human pathogens.